Behavioral competencies, determining the existence of a gap between academia and the IT job market - Ortiz Acuña, Cindy (2023)
In order to identify the relevant behavioral competencies for IT professionals and determine if there is a gap between the competencies developed by academia and those required by the job market in Costa Rica, this article analyses four stakeholder groups: literature, job boards, the graduation profiles of IT programs in public universities, and the directors and academic coordinators of these universities. The analysis identified 45 behavioral competencies, of which only three coincided in their categorization as having a high or moderate degree of importance. Notably, the analysis found no homogeneous competencies for all the investigated groups.